LINGUISTIC BARRIERS IN ENGINEERING COMMUNICATION / BARRIERES LINGUISTIQUES DANS LA COMMUNICATION EN INGENIERIE - Costeleanu Mirela (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2021)
Being able to communicate effectively is regarded as one of the most important life skills to acquire. Having good communication skills helps in all aspects of life - from personal to professional life. Poor communication in the workplace can lead to misunderstandings, frustration, confusion as well as to a tense environment which does not encourage employees to be productive and open to collaboration. Besides solid technical knowledge, engineering employers attach a lot of importance to strong communication skills which are becoming imperative as the enginering industry continues to evolve. Unfortunately, there is evidence that most graduate engineers lack the communication skills they need in the workplace. An employer who sees improving communication skills as a top priority and invests time and effort in reaching this objective is an asset to any organisation.